Effectiveness of the Project-Based Learning Model Using the Puzzle Adventure Educational Game on Critical Thinking Skills in Middle School Students - Aini Christin Nur; Warli Warli (Tarbiyah : Jurnal Ilmiah Kependidikan, 2026)
This research emphasizes the necessity of cultivating 21st-century competencies, particularly critical thinking, in order to confront global challenges and expedite technological advancements. The integration of educational puzzle adventure games with the Project Based Learning (PjBL) model is an innovative approach that has been investigated. The study aims to determine whether this model effectively improves the critical thinking skills of junior high school pupils by fostering active engagement in game-based project learning. The study, which was conducted using a quasi-experimental method with a one-group pre-test and post-test design, involved 33 eighth-grade pupils at UPT SMP Negeri 2 Palang. Ennis's indicators were employed to develop critical thinking evaluations, as well as engagement questionnaires and observations. The findings indicated a substantial rise in students' critical thinking scores, which rose from 4.79 to 8.24. This enhancement was verified by a paired sample t-test, which yielded a significance value of 0.000 (p < 0.05), suggesting that the learning model had a substantial positive effect. The results indicate that the PjBL model, which is based on puzzle adventure games, is effective in enhancing the critical thinking skills of students. An engaging and inventive alternative for 21st-century learning, this approach is particularly well-suited for middle school students in the digital era.